Rippling life on a dormant planet: hibernation of ribosomes, RNA polymerases, and other essential enzymes - Helena-Bueno, Karla; Chan, Lewis I.; Melnikov, Sergey V. (Frontiers in Microbiology, 2024)
Throughout the tree of life, cells and organisms enter states of dormancy or hibernation as a key feature of their biology: from a bacterium arresting its growth in response to starvation, to a plant seed anticipating placement in fertile ground, to a human oocyte poised for fertilization to create a new life. Recent research shows that when cells hibernate, many of their essential enzymes hibernate too: they disengage from their substrates and associate with a specialized group of proteins known as hibernation factors. Here, we summarize how hibernation factors protect essential cellular enzymes from undesired activity or irreparable damage in hibernating cells. We show how molecular hibernation, once viewed as rare and exclusive to certain molecules like ribosomes, is in fact a widespread property of biological molecules that is required for the sustained persistence of life on Earth.